The role of nurses in the family health strategy in the management of women with altered results of colpocytology (Research, Society and Development, 2020)
Objectives: To analyze, based on the literature, the role of nurses in the family health strategy in the management of women with results of altered Pap smear tests. Methodology:  It is an integrative literature review, with a qualitative approach. Based on the materials available in the Virtual Health Library. Selected articles published in the period 2015 to 2020, in full text, in Portuguese, Spanish and English languages ​​related to the proposed theme were selected. Results: The results point to a flawed health system in relation to the delay in following important appointments for treatment, in addition to the adherence and perception of women about the Pap smear is linked to multiple factors that prevent the control of the cancer of the cérvix and the importance of the nurse in cervical cancer control actions to reduce the incidence of cancer. Final considerations: The study made it possible to understand the reasons for the cancer of the cérvix screening to be inadequate, the reasons that lead to low levels of Pap smear tests, the role of nurses in cervical cancer control actions and their role in the proper management of altered results.